Altered Degranulation and pH of Neutrophil Phagosomes Impacts Antimicrobial Efficiency in Cystic Fibrosis - Hayes, Elaine; Murphy, Mark P.; Pohl, Kerstin; Browne, Niall; McQuillan, Karen; Saw, Le Er; Foley, Clare; Gargoum, Fatma; McElvaney, Oliver J.; Hawkins, Padraig; Gunaratnam, Cedric; McElvaney, Noel G.; et al. (Frontiers in Immunology, 2020)
Studies have endeavored to understand the cause for impaired antimicrobial killing by neutrophils of people with cystic fibrosis (PWCF). The aim of this study was to focus on the bacterial phagosome. Possible alterations in degranulation of cytoplasmic granules and changes in pH were assessed. Circulating neutrophils were purified from PWCF (n=28), PWCF receiving ivacaftor therapy (n=10) and healthy controls (n=28). Degranulation was assessed by Western blot analysis and flow cytometry. The pH of phagosomes was determined by use of BCECF-AM-labelled Staphylococcus aureus or SNARF labelled Candida albicans. The antibacterial effect of all treatments tested was determined by colony forming units enumeration. Bacterial killing by CF and healthy control neutrophils were found to differ (p<0.0006). By use of flow cytometry and subcellular fractionation the kinetics of intraphagosomal degranulation were found to be significantly altered in CF phagosomes, as demonstrated by increased primary granule CD63 (p=0.0001) and myeloperoxidase (MPO) content (p=0.03). In contrast, decreased secondary and tertiary granule CD66b (p=0.002) and decreased hCAP-18 and MMP-9 (p=0.02), were observed. After 8 min phagocytosis the pH in phagosomes of neutrophils of PWCF was significantly elevated (p=0.0001), and the percentage of viable bacteria was significantly increased compared to HC (p=0.002). Results demonstrate that the recorded alterations in phagosomal pH generate suboptimal conditions for MPO related peroxidase, and alpha-defensin and azurocidine enzymatic killing of Staphylococcus aureus and Pseudomonas aeruginosa. The pattern of dysregulated degranulation and prolonged phagosomal alkalinization in CF neutrophils were normalized in vivo following treatment with the ion channel potentiator ivacaftor (p=0.04). Our results confirm that alterations of circulating neutrophils from PWCF are corrected by CFTR modulator therapy, but raise a question related to proton channel expression or delayed activity in CF.